Conversational Speech Transcription Using Context-Dependent Deep Neural Networks - Yu, Dong; Seide, Frank; Li, Gang (ICML 2012, 2012)
Context-Dependent Deep-Neural-Network HMMs, or CD-DNN-HMMs, combine the classic artificial-neural-network HMMs with traditional context-dependent acoustic modeling and deep-belief-network pre-training. CD-DNN-HMMs greatly outperform conventional CD-GMM (Gaussian mixture model) HMMs: The word error rate is reduced by up to one third on the difficult benchmarking task of speaker-independent single-pass transcription of telephone conversations.